'Refugees welcome?' The interplay between perceived threats and general concerns on the acceptance of refugees – a factorial survey approach in Germany. Issue 3 (17th February 2019) - von Hermanni, Hagen; Neumann, Robert
ABSTRACT: The on-going migration of refugees to Europe has fuelled debates about the indigence of refugees and the perceived legitimacy of individual claims for asylum in different receptive countries. With a substantial body of research that has investigated the antecedents of attitudes towards immigrants, evidence on whether those underlying assumptions hold true for refugees as well remains scarce. The paper applies the framework of Intergroup Threat Theory to arrive at competing hypotheses with regard to the acceptance levels of refugees. We use pooled data from two probabilistic samples drawn in the German city of Dresden and apply a confounded factorial survey design to extend previous research on attitudes towards refugees. We find that natives perceive political persecution and war as justified reasons for seeking asylum in Germany, while socio-demographic characteristics of respondents and refugees are of minor importance. Foremost, the individual level of respondent's fear of crime represents a crucial moderator of the perception of refugees as threatening.